Pengaruh Model Pembelajaran Problem Based Learning Terhadap Pemahaman Konsep IPA Siswa Kelas 4 SD Negeri Doyong 4 Kota Tangerang - Hidayati, Nurul Dwi; Sunardin, Sunardin; Magdalena, Ina (Peneliti.net, 2023)
Nurul Dwi Hidayati